Childhood Circumstances and Adult Outcomes: Act II - Almond, Douglas; Currie, Janet; Duque, Valentina (Journal of Economic Literature, 2018)
That prenatal events can have life-long consequences is now well established. Nevertheless, research on the fetal origins hypothesis is flourishing and has expanded to include the early childhood (postnatal) environment. Why does this literature have a “second act?” We summarize the major themes and contributions driving the empirical literature since our 2011 reviews, and try to interpret the literature in light of an overarching conceptual framework about how human capital is produced early in life. One major finding is that relatively mild shocks in early life can have substantial negative impacts, but that the effects are often heterogeneous reflecting differences in child endowments, budget constraints, and production technologies. Moreover, shocks, investments, and interventions can interact in complex ways that are only beginning to be understood. Many advances in our knowledge are due to increasing accessibility of comprehensive administrative data that allow events in early life to be linked to long-term outcomes. Yet, we still know relatively little about the interval between, and thus about whether it would be feasible to identify and intervene with affected individuals at some point between early life and adulthood. We do know enough, however, to be able to identify some interventions that hold promise for improving child outcomes in early life and throughout the life course. (JEL I12, J13, J16, Q51, Q53)